An Analysis of Dust Explosion Incidents in Industries and Mitigation Best Practices within Malaysia - Mohd Azimie, Ahmad; Norazura, Ismail; Mohamad Rizza, Othman (Universiti Malaysia Pahang, 2016)
The trends of process safety incident have been put in the statistical research and development in order to prevent and mitigate the phenomenon. One of the incident are known as dust explosion that represent a constant hazard to industries including any manufacturing using and handling of combustible dust materials. Lack of sharing and know how on best practices in managing the workplace to avoid this phenomenon happening throughout the industries. The severity and the consequences of not practicing it before it happens were not been fore seen by the process team until it too late. This present paper discusses the best practices in managing the hazards from the catastrophes to be happening again. In addition, the mitigation response was also being explored thoroughly by database of best practices. The work summarizes in Microsoft Access database related to incident were tabulated according to the types of industries involved in dust explosion, the equipment that involved, the types of combustible dust, the sources of ignition points, and also the impact from the incident. All incident being summarized from the literature review and also documentation review respectively. Triangulation method was used in managing the data and verified with industries by having interview session, observation and documentation review.